Changes in Muscle Oxygen Saturation Have Low Sensitivity in Diagnosing Chronic Anterior Compartment Syndrome of the Leg. (6th January 2016) - Rennerfelt, Kajsa; Zhang, Qiuxia; Karlsson, Jón; Styf, Jorma
Abstract : Background: Near-infrared spectroscopy measures muscle oxygen saturation (StO2 ) in the skeletal muscle and has been proposed as a noninvasive tool for diagnosing chronic anterior compartment syndrome (CACS). The purpose of this study was to investigate the diagnostic value of changes in StO2 during and after exercise in patients with CACS. Methods: The study comprised 159 consecutive patients with exercise-induced leg pain. Near-infrared spectroscopy was used to measure StO2 continuously before, during, and after an exercise test. One minute post-exercise, intramuscular pressure was recorded in the same muscle. The cohort was divided into patients with CACS (n = 87) and patients without CACS (n = 72) according to the CACS diagnostic criteria. Reoxygenation at rest after exercise was calculated as the time period required for the level of muscular StO2 to reach 50% (T50 ), 90% (T90 ), and 100% (T100 ) of the baseline value. Results: The lowest level of StO2 during exercise was 1% (range, 1% to 36%) in the patients with CACS and 3% (range, 1% to 54%) in the patients without CACS. The sensitivity was 34% and the specificity was 43% when an StO2 level of ⩽8% at peak exercise was used to indicate CACS. The sensitivity and the specificity were only 1% when an StO2 level of ⩽50% at peak exercise was used to indicate CACS. The time period for reoxygenation was seven seconds (range, one to forty-three seconds) at T50, twenty-eight seconds (range, seven to seventy-seven seconds) at T90, and forty-two seconds (range, seven to 200 seconds) at T100 in the patients with CACS and ten seconds (range, one to forty-nine seconds) at T50, thirty-two seconds (range, four to 138 seconds) at T90, and forty-eight seconds (range, four to 180 seconds) at T100 in the patients without CACS. When thirty seconds or more at T90 was set as the cutoff value for a prolonged time for reoxygenation, indicating a diagnosis of CACS, the sensitivity was 38% and the specificity was 50%. Conclusions: Changes in muscle oxygen saturation during and after an exercise test that elicits leg pain cannot be used to distinguish between patients with CACS and patients with other causes of exercise-induced leg pain. Level of Evidence: DiagnosticLevel II . See Instructions for Authors for a complete description of levels of evidence.